Comparison of the antioxidant activity and total phenolic, flavonoid content of aerial part of Cleome viscosa L. - Prakash Chandra Gupta; Nisha Sharma; Ch.V. Rao (International Journal of Phytomedicine, 2011)
Cleome viscosa L. (Capparidaceae), commonly known as “wild mustard”, is an annual, sticky herb found as common weed all over the plains of India and throughout the tropics of the world. In traditional systems of medicine the plant is reported to possess beneficial effects as an anthelmintic, antiseptic, carminative, antiscorbutic, febrifuge, and cardiac stimulant. The aim of the present study was to evaluate the antioxidant activity of 70% methnolic extract of leaf and stem part of Cleome viscosa (CV) by using different in vitro model such as β carotene bleaching assay, reducing power and free radical scavenging activity (DPPH and hydroxyl radical scavenging activity). Total phenolic content were estimated by the Folin–Ciocalteu colorimetric method using gallic acid as standard and expressed as mg/g gallic acid equivalent (GAE) and total flavonoid content was estimated by aluminium chloride colourimetric method. The total phenolic, flavonoid content and antioxidant activity of Cleome viscosa leaves were found to be 66.38±0.82mg/g, 0.54±0.04mg/g and 77.30% respectively. Cleome viscosa leaves showed high free radical scavenging activity as evidenced by the low IC50 values in both DPPH (1,1-diphenyl-2-picryl hydrazyl) (373.18 μg/ml) and hydroxyl radical (573.55 μg/ml) methods. Cleome viscosa leaves possess high phenolic, flavonoid content and potential antioxidant activity, reducing power and free radical scavenging activity in comparison to stem.